Geographical phytodiversity of Miralrío compared with flora of western «la Alcarria» of Guadalajara province. Taxonomic and vascular richness analysis - Juan Javier García-Abad Alonso; Josep María Panareda Clopés (Boletín de la Asociación de Geógrafos Españoles)
Resumen